Optimal. Leaf size=24 \[ 2-(4-x) \left (-2+3^{-3+2 \log \left (x^2\right )}-x\right ) \]
________________________________________________________________________________________
Rubi [A] time = 0.09, antiderivative size = 31, normalized size of antiderivative = 1.29, number of steps used = 7, number of rules used = 5, integrand size = 37, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.135, Rules used = {14, 2274, 12, 15, 43} \begin {gather*} \frac {1}{27} x \left (x^2\right )^{\log (9)}-\frac {4}{27} \left (x^2\right )^{\log (9)}-(1-x)^2 \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 12
Rule 14
Rule 15
Rule 43
Rule 2274
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \left (-2 (-1+x)+\frac {3^{-3+2 \log \left (x^2\right )} (-16 \log (3)+x (1+\log (81)))}{x}\right ) \, dx\\ &=-(1-x)^2+\int \frac {3^{-3+2 \log \left (x^2\right )} (-16 \log (3)+x (1+\log (81)))}{x} \, dx\\ &=-(1-x)^2+\int \frac {\left (x^2\right )^{2 \log (3)} (-16 \log (3)+x (1+\log (81)))}{27 x} \, dx\\ &=-(1-x)^2+\frac {1}{27} \int \frac {\left (x^2\right )^{2 \log (3)} (-16 \log (3)+x (1+\log (81)))}{x} \, dx\\ &=-(1-x)^2+\frac {1}{27} \left (x^{-4 \log (3)} \left (x^2\right )^{2 \log (3)}\right ) \int x^{-1+4 \log (3)} (-16 \log (3)+x (1+\log (81))) \, dx\\ &=-(1-x)^2+\frac {1}{27} \left (x^{-4 \log (3)} \left (x^2\right )^{2 \log (3)}\right ) \int \left (-16 x^{-1+4 \log (3)} \log (3)+x^{\log (81)} (1+\log (81))\right ) \, dx\\ &=-(1-x)^2-\frac {4}{27} \left (x^2\right )^{\log (9)}+\frac {1}{27} x \left (x^2\right )^{\log (9)}\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.10, size = 23, normalized size = 0.96 \begin {gather*} 3^{-3+2 \log \left (x^2\right )} (-4+x)+2 x-x^2 \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.70, size = 27, normalized size = 1.12 \begin {gather*} -x^{2} + {\left (x - 4\right )} e^{\left (2 \, \log \relax (3) \log \left (x^{2}\right ) - 3 \, \log \relax (3)\right )} + 2 \, x \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.41, size = 32, normalized size = 1.33 \begin {gather*} -x^{2} + \frac {1}{27} \, x e^{\left (2 \, \log \relax (3) \log \left (x^{2}\right )\right )} + 2 \, x - \frac {4}{27} \, e^{\left (2 \, \log \relax (3) \log \left (x^{2}\right )\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.11, size = 23, normalized size = 0.96
method | result | size |
risch | \(-x^{2}+2 x +\frac {\left (x -4\right ) \left (x^{2}\right )^{2 \ln \relax (3)}}{27}\) | \(23\) |
norman | \({\mathrm e}^{2 \ln \relax (3) \ln \left (x^{2}\right )-3 \ln \relax (3)} x +2 x -x^{2}-4 \,{\mathrm e}^{2 \ln \relax (3) \ln \left (x^{2}\right )-3 \ln \relax (3)}\) | \(42\) |
default | \(2 x +\frac {3^{2 \ln \left (x^{2}\right )-4 \ln \relax (x )} x \,{\mathrm e}^{4 \ln \relax (3) \ln \relax (x )}}{108 \ln \relax (3)+27}-\frac {4 \,{\mathrm e}^{4 \ln \relax (3) \ln \relax (x )} 3^{2 \ln \left (x^{2}\right )-4 \ln \relax (x )}}{27}+\frac {4 \,3^{2 \ln \left (x^{2}\right )-4 \ln \relax (x )} \ln \relax (3) x \,{\mathrm e}^{4 \ln \relax (3) \ln \relax (x )}}{27 \left (4 \ln \relax (3)+1\right )}-x^{2}\) | \(99\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [B] time = 0.62, size = 58, normalized size = 2.42 \begin {gather*} -x^{2} + \frac {4 \, x e^{\left (4 \, \log \relax (3) \log \relax (x)\right )} \log \relax (3)}{27 \, {\left (4 \, \log \relax (3) + 1\right )}} + 2 \, x + \frac {x e^{\left (4 \, \log \relax (3) \log \relax (x)\right )}}{27 \, {\left (4 \, \log \relax (3) + 1\right )}} - \frac {4}{27} \, e^{\left (2 \, \log \relax (3) \log \left (x^{2}\right )\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 1.09, size = 30, normalized size = 1.25 \begin {gather*} 2\,x-\frac {4\,{\left (x^2\right )}^{2\,\ln \relax (3)}}{27}-x^2+\frac {x\,{\left (x^2\right )}^{2\,\ln \relax (3)}}{27} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.81, size = 32, normalized size = 1.33 \begin {gather*} - x^{2} + \frac {x e^{4 \log {\relax (3 )} \log {\relax (x )}}}{27} + 2 x - \frac {4 e^{4 \log {\relax (3 )} \log {\relax (x )}}}{27} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________